2019
DOI: 10.1002/dta.2583
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry and pharmacology of putative synthetic cannabinoid receptor agonist (SCRA) new psychoactive substances (NPS) 5F‐PY‐PICA, 5F‐PY‐PINACA, and their analogs

Abstract: 5F‐PY‐PICA and 5F‐PY‐PINACA are pyrrolidinyl 1‐(5‐fluoropentyl)ind (az)ole‐3‐carboxamides identified in 2015 as putative synthetic cannabinoid receptor agonist (SCRA) new psychoactive substances (NPS). 5F‐PY‐PICA, 5F‐PY‐PINACA, and analogs featuring variation of the 1‐alkyl substituent or contraction, expansion, or scission of the pyrrolidine ring were synthesized and characterized by nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography–quadrupole time‐of‐flight–mass spectrometry (LC–QTOF–MS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 49 publications
5
30
0
Order By: Relevance
“…( R )-AMB-FUBINACA tested in this study was more potent than any other ( R )-enantiomer in this study and was more potent than both the indazole-3-carboxamides, ( S )-JWH-018 (control, this study) and ( S )-AB-PINACA (6) and the indole-3-carboxamides 5F-AMB-PICA and 5F-PY-PICA analyzed previously using the same assay under the same conditions (Noble et al, 2019). The latter compound has been found to have little or no CB 1 activity, a finding confirmed by Banister et al (2019a).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…( R )-AMB-FUBINACA tested in this study was more potent than any other ( R )-enantiomer in this study and was more potent than both the indazole-3-carboxamides, ( S )-JWH-018 (control, this study) and ( S )-AB-PINACA (6) and the indole-3-carboxamides 5F-AMB-PICA and 5F-PY-PICA analyzed previously using the same assay under the same conditions (Noble et al, 2019). The latter compound has been found to have little or no CB 1 activity, a finding confirmed by Banister et al (2019a).…”
Section: Resultsmentioning
confidence: 55%
“…In 2015, the production and export of 116 NPS were controlled by China including 39 SCRAs (UNODC, 2015) and soon after many of these, if not all, disappeared from the market. These compounds were rapidly replaced by new analogs, and in many but not all cases, these new substances have generally been more potent (Banister and Connor, 2018b; Banister et al, 2019a,b; Noble et al, 2019). It is therefore important to develop robust and adaptable methodologies to carry out detailed analytical and pharmacological profiling of new substances as they appear on the illicit drug market and to determine the relative theoretical potency of materials containing SCRAs at all levels of the supply chain for harm reduction purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that various metabolites of synthetic cannabinoids retain some cannabimimetic activity, indicating that they could contribute to the pharmacological effects of the drugs (Longworth et al 2017). In contrast, some substances that are promoted as cannabinoid designer drugs have only low in vitro affinity for cannabinoid receptors and fail to exert significant cannabinoid activity in vivo, thus calling into question their classification as synthetic cannabinoids (Banister et al 2019b). Only a few synthetic cannabinoids have been studied to date with regard to their interactions with noncannabinoid targets, with low or no affinity for most major neurotransmitter receptors (Wiley et al 2016).…”
Section: Mechanism Of Action Of Synthetic Cannabinoidsmentioning
confidence: 99%
“…Two related compounds, MDMB-FUBINACA and 5-fluoro AMB, have similarly been shown to produce profound hypothermic responses in Long-Evans rats at these doses 15 . Structural analogues of these ligands, such as XLR-11 39 , 5-fluoro CUMYL-P7AICA 16 , CUMYL-4CN-BINACA 40 , and AB-CHMINACA, and AB-PINACA 41 have shown similar cannabimimetic effects in rodent models—including profound hypothermia and pro-convulsant effects. Here, in vitro and in silico experiments utilized human CB1R and CB2R, whereas in vivo experiments were conducted in mice, which represents a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%